Narra Quito: estrategia educomunicacional para la apropiación del patrimonio cultural (Miscelánea) - Samudio Granados, Marcela (2026)
The Narra Quito transmedia project is an educommunicational experience for the appropriation of intangible cultural heritage by Ecuadorian citizens. Narra Quito seeks to unearth stories that have been historically invisible or silent: stories of families; of urban and rural populations; of persons from low social strata; of childhood and adolescence; of those who handle knowledge that does not pass through writing; etc. In short, stories of those who build the cultural and agri-food heritage of Quito, but who have not necessarily been heard and acknowledged. The goal of this article is to analyze the experience and influence of the project through a theoretical approach, starting from the review of the institutional motivations of the initiative, the components of the transmedia project, the different languages and media support used, and the ways of relating with those who contribute and participate in the project. Thus, through a mixed methodology, the influence that Narra Quito has had on its audiences is determined. The results show a high level of interest and a positive evaluation of the platform, although challenges are identified in content creation by its users. It is concluded that, while educommunication strategies are effective for the revalorization of heritage, more robust mechanisms are needed to encourage active co-creation.